Preliminary design of sliding mode controller for angular positional tracking of an aircraft - Jones, Lim Jen Nee; Tan, Chee Pin; Man, zhihong; Akmeliawati, Rini (2009)
Sliding mode controllers are known to be robust to parameter changes and capable of rejecting disturbances. Most sliding mode controllers were implemented on aircraft models that were derived based on the aircraft's body axes. The aircraft model in this paper are derived from an energy based modeling technique where the aircraft dynamics can be defined by Euler-Lagrangian equations that makes decoupling of aircraft dynamics simple and straightforward. It is possible to do so since these equations can be derived from the inertial axes of the aircraft instead of the aircraft's body axes. The nature of these equations makes it easy to implement the sliding mode controller on all the angular positions of the aircraft for the purpose of tracking a reference trajectory. Parameter changes and disturbances were also introduced as part of the evaluation procedure in few sets of simulations to prove how well these angular positions can be tracked. The controller designed to achieve angular positional tracking includes a nominal feedback controller and a sliding mode compensator. The performance of the controller presented are measured using root-mean-square error values and maximum errors for roll, pitch and yaw. Results presented shows good tracking performances throughout entire flight trajectory that includes a one-sided engine failure, a 90 degree turn and rotations in the pitch angle.